Urtica praetermissa (Urticaceae): a new species from central Mexico - Steinmann, Victor W. (Instituto de Ecología, A.C., 2004)
Urtica praetermissa (Urticaceae), a new species from central Mexico, is described and illustrated. It occurs in the trans-Mexican volcanic belt and the Sierra Madre del Sur in the Distrito Federal and the states of Guerrero, Mexico, and Michoacan. It grows at elevations from 2000 to 3100 m in forests of Abies and Quercus-Pinus, as well as scrub derived from these types of vegetation. Two subspecies are proposed: ssp. michoacana and spp. praetermissa. These taxa are separated by characteristics of the stipules: connate in the former and free in the latter. The species appears most similar to U. mexicana but differs in possessing larger achenes and inflorescences that are either completely unisexual or bisexual with the staminate and pistillate flowers intermixed along its entire length.